New developments in incremental heating detrital 40Ar∕39Ar lithic (DARL) geochronology using Icelandic river sand - O. Okwueze; K. Konrad; K. Konrad; T. Capaldi; T. Capaldi (Geochronology)
Iceland records over 15 million years of complex volcanism resulting from the intersection of a mid-ocean ridge and mantle plume upwelling. The Iceland mantle plume has been active for at least 70 Myr, with surface expressions in Greenland, the North Atlantic, and Iceland. The Iceland hotspot may exhibit periods of increased volcanic output linked to pulses of upwelling within the plume. Understanding Iceland's magmatic history and potential pulsation could provide key insights into dynamic topography driving changes in deep-water oceanic circulation, late Cenozoic climate change, and mantle plume–mid-ocean ridge interaction. Detrital geochronology is a powerful tool for capturing the magmatic history of a region. However, Iceland's fine-grained extrusive volcanic lithologies lack the typical detrital mineral phases such as zircon, sanidine, hornblende, and rutile that current geochronology methods utilize. Here we present a new methodology for capturing the magmatic history of fine-grained extrusive volcanic rocks using single-grain detrital 40Ar/39Ar<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="49pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="644829f092a7f46da57c485ba10d080e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gchron-6-683-2024-ie00004.svg" width="49pt" height="15pt" src="gchron-6-683-2024-ie00004.png"/></svg:svg> incremental heating geochronology. The DARL (or detrital argon lithic) method consists of 40Ar/39Ar<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="49pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="be50c6085c96da3cf61bab29242a7248"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gchron-6-683-2024-ie00005.svg" width="49pt" height="15pt" src="gchron-6-683-2024-ie00005.png"/></svg:svg> incremental heating and total fusion analyses on single lithic grains, which has not yet been applied to predominantly mafic terrains composed of young glassy lava flows that commonly display sub-atmospheric 40Ar/36Ar<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="49pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="37597376acd6c8fdce5fd6da8a8114b5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gchron-6-683-2024-ie00006.svg" width="49pt" height="15pt" src="gchron-6-683-2024-ie00006.png"/></svg:svg> isochron intercepts and low 40Ar∗. This work represents an 40Ar/39Ar<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="49pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="103bb0deb6c931850b460c38cc0982c9"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gchron-6-683-2024-ie00007.svg" width="49pt" height="15pt" src="gchron-6-683-2024-ie00007.png"/></svg:svg> incremental heating pilot study on 19 single grains of Icelandic river sand and fine gravel (1–3 mm) collected from five different catchments. A total of 15 of the 19 basaltic grains produced concordant age experiments that ranged from 0.2 to 13.5 Ma and uncertainties (2σ) from 1 % to 86 %, with the grains under 1 Ma having the largest uncertainties. Preliminary results show that basaltic grains with less alteration (and corresponding lower atmospheric argon concentration) yield more accurate age determinations, though altered basaltic grains can still produce statistically valid age determinations. Results presented here show the validity of the incremental heating DARL methodology for capturing the magmatic history of mafic terrains. The long analysis time required for incremental heating experiments makes it infeasible to produce the large number of ages required for a detrital study. For this reason, we build upon a previously proposed method that combines total fusion and incremental heating DARL methodologies to acquire age data for the large N values needed for detrital studies of mafic volcanic terrains.